Working animal welfare and their multidimensional roles on livelihood improvement in Ethiopia: A systematic review and meta-analysis - Getasew Daru Tariku; Tarekegn Derbib Biza; Senait Kehali Tesfaye; Sinkie Alemu Kebede (Animal Welfare)
Working animals have a crucial socio-economic role to play for many low-income communities. One such example is in Ethiopia where virtually all the draught power for agricultural production derives from working animals. However, despite this, the welfare status of working animals in this country remains poor. Hence, a clear understanding of the major welfare problems faced by working animals is key to helping improve their welfare status and to maximise their economic contribution. This systematic literature review encompasses 28 studies published between 2010–2024, that address the role of working animals and the factors impinging on their welfare. Suitability of papers for inclusion (and exclusion) involved use of a PRISMA flow diagram. In this review, we also sought to define the exact role of working animals with them found to be used not only for draught power but also as a direct source of food as well as income. A lack of medical care was also highlighted with animals afforded limited access to feed and water, subjected to regular physical abuse, and deprived of access to shelter. Insufficient assessment of welfare and improper methods of data analysis were also found to be an issue, factors that require to be addressed by future researchers to help improve the welfare of working animals in this region